Central control of autonomic functions in health and disease - Stuart J. McDougall (Frontiers Research Topics, 2015)
The field of autonomic neuroscience research concentrates on those neural pathways and processes that ultimately modulate parasympathetic and sympathetic output to alter peripheral organ function. In the following ebook, laboratories from across the field have contributed reviews and original research to summarize current views on the role of the brain in tuning peripheral organ performance to regulate body temperature, glucose homeostasis and blood pressure.